A Useful Tool As a Medical Checkup in a General Population—Bioelectrical Impedance Analysis - Enomoto, Mika; Adachi, Hisashi; Fukami, Ako; Kumagai, Eita; Nakamura, Sachiko; Nohara, Yume; Kono, Shoko; Nakao, Erika; Morikawa, Nagisa; Tsuru, Tomoko; Sakaue, Akiko; Fukumoto, Yoshihiro (Frontiers in Cardiovascular Medicine, 2017)
Accumulation of visceral fat leads to metabolic syndrome and increases risks of cerebro-cardiovascular diseases, which should be recognized and improved at the early stage in general population. Accurate measurement of visceral fat area (VFA) is commonly performed by the abdominal cross-sectional image measured by computed tomography scan, which is, however, limited due to the radiation exposure. The bioelectrical impedance analysis (OMRON, HDS-2000 DUALSCANR) has been recently developed to measure VFA, which is more easily accessible modality. In the present study, we investigated the clinical usefulness of DUALSCANR in 226 subjects who received health examination, including blood chemistries, electrocardiography, cardio, and carotid ultrasonography. VFA was measured within only just 5 min. Average of VFA was 83.5 ± 36.3 cm2 in men, and 64.8 ± 28.0 cm2 in women, which was correlated to weight (r = 0.7404, p < 0.0001), body mass index (BMI) (r = 0.7320, p < 0.0001), and waist circumstance (r = 0.7393, p < 0.0001). In multivariate analyses, VFA was significantly associated with weight (p < 0.0001), BMI (p < 0.0001), and waist circumstance (p < 0.0001). Compared to the group of smaller waist and normal BMI, VFA was significantly increased (p < 0.0001) in the group of larger waist and obese subjects. In conclusion, these results indicated that DUALSCANR is useful to measure VFA easily in general population, even in a large number of subjects.